2020
DOI: 10.1192/j.eurpsy.2020.73
|View full text |Cite
|
Sign up to set email alerts
|

Linking language features to clinical symptoms and multimodal imaging in individuals at clinical high risk for psychosis

Abstract: Background. Abnormalities in the semantic and syntactic organization of speech have been reported in individuals at clinical high-risk (CHR) for psychosis. The current study seeks to examine whether such abnormalities are associated with changes in brain structure and functional connectivity in CHR individuals. Methods. Automated natural language processing analysis was applied to speech samples obtained from 46 CHR and 22 healthy individuals. Brain structural and resting-state functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Speci cally, we posit that gures of speech wield signi cant in uence, yet their extraction using quantitative methodologies is challenged by their reliance on external world knowledge. Moreover, in alignment with the suggestions and practices of prior research 45,46 , we hold the belief that a multimodal model incorporating speech and video data holds immense potential in yielding insights in spite of drawbacks associated with data privacy.…”
Section: Discussionmentioning
confidence: 52%
“…Speci cally, we posit that gures of speech wield signi cant in uence, yet their extraction using quantitative methodologies is challenged by their reliance on external world knowledge. Moreover, in alignment with the suggestions and practices of prior research 45,46 , we hold the belief that a multimodal model incorporating speech and video data holds immense potential in yielding insights in spite of drawbacks associated with data privacy.…”
Section: Discussionmentioning
confidence: 52%
“…Andreasen, 1979). However, this assumption has only inconsistently been supported by the literature, with highly varying statistical significance and size of the effects found across studies: while some studies found a strong correlation between semantic coherence and measures of formal thought disorder (Bilgrami et al, 2022; Elvevåg et al, 2007), most others reported uncertain results (Bedi et al, 2015; Haas et al, 2020; Just et al, 2020; Morgan et al, 2021; Pauselli et al, 2018; Sarzynska-Wawer et al, 2021; Tang et al, 2021). Our study emphasized the lack of a clear picture.…”
Section: Discussionmentioning
confidence: 99%
“…However, a critical obstacle to any concrete use of these findings is that it is not clear whether the findings would replicate and generalize to new samples and populations, an overarching problem for clinical and social sciences (Hitczenko et al, 2021; Parola et al, 2020; Rocca & Yarkoni, 2021; Rybner et al, 2021). Indeed, a closer look reveals clearly contradictory results: linguistic measures are inconsistently associated with symptoms, and findings vary across different rating scales and samples (Bedi et al, 2015; Corcoran et al, 2018; Haas et al, 2020; Morgan et al, 2021; Pauselli et al, 2018; Sarzynska-Wawer et al, 2021; Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…22 Therefore, greater precision may be achieved by modeling specific types of speech disturbance, rather than diagnostic phenotypes as a whole. [22][23][24] Second, speech disturbances may be shared across disorders, with implications for underlying neurobiology. We need to define cross-diagnostically diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…22 Therefore, greater precision may be achieved by modeling specific types of speech disturbance, rather than diagnostic phenotypes as a whole. 2224 Second, speech disturbances may be shared across disorders, with implications for underlying neurobiology. We need to define cross-diagnostically valid constructs in order to determine whether speech features can be used consistently across disorders as biomarkers for particular speech phenotypes.…”
Section: Introductionmentioning
confidence: 99%